The Practice of Dentistry by Australian- and Overseas-Trained Dentists in Australia: Discriminant Analysis of key Predictors - Madhan Balasubramanian; A. John Spencer; Woosung Sohn; David S. Brennan (Elsevier, 2021)
Introduction: Overseas-trained dentists comprise at least one-fourth of the overall Australian dental workforce. This study examined characteristics and practice differences between Australian- and overseas-trained dentists to identify key predictors that best differentiate their dentistry practices. Methods: Data for the study were from the Longitudinal Study of Dentist Practice Activity (LSDPA), a survey of a nationally representative random sample of dentists in Australia commencing in 1983-1984 and repeated every 5 years. Dentists were surveyed on a wide range of items including participant characteristics, practice patterns, practice inputs, direct demand, and productivity measures. Data were weighted to provide national estimates by age, sex, and practice type. Discriminant function analysis was used to examine the predictor variables that best distinguished between the two groups. Analysis was limited to the most recent wave of the study. Results: A total of 1148 dentists (response rate = 67%) responded to the survey in 2009-2010; 648 cases were available for the discriminant analysis. The discriminant functions for the full sample and each of the 3 age groups (<35 years; 35-50 years; and 50+ years) were found effective to separate dentists into 2 groups (Australian and overseas), with the proportion of cases correctly classified being highest for the oldest age group (89.7% for 50+ years). Female gender, type of practice (working in public sector), and working in disadvantaged areas were significant predictors, with more prominence in the 35- to 50-year age group. Practice inputs, demand, and productivity measures offered less discriminative capacity between the dentists. Conclusion: Overseas-trained dentists contribute towards providing dental care to underserved populations, the public sector, and in rural and remote locations. This study provided basis to argue that policies to encourage overseas-trained dentists to contribute towards areas of need locations have been successful, and key productivity measures were also similar to Australian-trained dentists.